Reduced heart rate variability during mania in a repeated naturalistic observational study - Stautland, Andrea; Jakobsen, Petter; Fasmer, Ole Bernt; Osnes, Berge; Torresen, Jim; Nordgreen, Tine; Oedegaard, Ketil J. (Frontiers in Psychiatry, 2023)
Background: Bipolar disorder (BD) is a chronic recurrent mood disorder associated with autonomic nervous system (ANS) dysfunction, indexed by heart rate variability (HRV). Changes in HRV between mood states are sparsely studied longitudinally. We aimed to compare HRV of hospitalized manic individuals with their own euthymic selves in a naturalistic observational study. Methods: 34 individuals were included, of which 16 were lost to follow-up. Ultimately 15 patients provided reliable heart rate data in both a manic and euthymic state, using photoplethysmography (PPG) sensor wristbands overnight. We calculated HRV measures Root Mean Square of Successive Differences (RMSSD), High-frequency (HF: 0.15-0.40Hz), Low-frequency (LF: 0.40-0.15Hz), Very low-frequency (VLF: 0.0033-0.04Hz), Total power and Sample Entropy in 5-minute night-time resting samples. We compared HRV measures by mood state within individuals using paired t-tests and linear regression to control for age and sex. Results: HRV was lower in the manic state when compared to the euthymic state for all HRV metrics (p≤0.02), with large to medium effect sizes (g=1.24 to 0.65). HRV changes were not significantly affected by age or sex. Conclusion: This longitudinal study provides evidence of lower HRV in manic states compared to euthymia, indicating an association between ANS dysregulation and changes in bipolar mood state. This corroborates previous cross-sectional studies, although the association may be less clear or reversed in hypomanic states. Further investigation in larger longitudinal samples is warranted.